THE AESTHETICS, RELIGIOSITY, AND RESPONSE OF THE READERS OF GEGURITAN SUCITA - Suka Yasa, I Wayan; Cika, I Wayan; Rai Sudharta, Tjokorda; Suarka, I Nyoman (e-Journal of Linguistics; Vol. 4. Januari 2010 No. 1)
The object of this research is the text of Geguritan Sucita having total versesof 1,877. The problem observed is that the structure, esthetic rule applied andsource of text transformation into GS as religion literature. The main objective ofthis research is to answer the three problems concerned. In addition, it has theobjective to preserve and develop geguritan literature. The benefit can be as oneof sources of knowledge in literary science, especially concerning geguritanliterature; as the consideration in making policy related to religion and Balineseculture; and also as reading material, especially for readers of geguritan literature.The theory applied in reviewing the three problems is structural, semiotic,intertext, rasa (mode) and literature reception. The data source obtained byconducting literature study, observation and interview. The data is the analyzedfrom literature and religion point of view. The research novelties are as follows :GS is gita puja of Ida Ketut Jlantik (1905-1961) which is offered to GodAlmighty. As worshipped song, GS is sekar. The materials are quoted fromclassical works of prior Hindu which is then arranged in accordance with idealismof writers kawi-wiku by considering rule of k?vya.GS is established using Balinese language Kepara enriched withvocabularies of Old Javanese so it has Hindu esthetic. Formal structure of GS isestablished according to geguritan : padalingsa matrix. The text consists of 1,877rhythm, 11 rhyme and 57 melodies. Sinom rhythm as the idol one to lead otherrhythm in order to s?nta rasa. Verses of GS can be grouped into two parts: 4rhythm manggala and) 1,873 narrative rhythm. Totally, formal structure of GSfulfills alamkara principle. the text has melody and euphony religious melody.Narrative structure GS is established following norm of tattwa purarbh?wa‘reborn cycle’, in addition it is the leader of rhythm as well as function as epilog.In term of contemplative reading level bhakti yoga, manggala is finally known asthe center text of GS.GS narration is developed according to aguron-guron rule‘having the teacher from spiritual and nyastra tradition. From matrix aguronguron,it is proposed two plots in paradox one: k?ma and tirtayatra. Plot sourceof k?ma is narrated by the existence of Sang Sucita. On the other hand, plot sourceof tirtayatra is narrated by the existence of Sang Subudi. K?ma (desire) and dilemma. Its message, if someone wish to succeed in reaching life objective, thetwo obstacles must firstly be defeated through learning process of mulat sarira byyoga : bhakti-karma-jnana- and yoga. After completion of narrating plot source oftirtayatra, it is also narrated k?ma which is developed into ahangkara. For thisreason, it is presented bad figure I Pataka to spread disaster which is in contrastwith the common rule of geguritan literature. GS narration can be understood asreading model according to narrative structure rule of k?vya. In every part ofstructure called sandhi is expressed rasa. There are nine rasa that can be enjoyedin GS. The nine rasa is inter-related and function collectively to strength the mainrasa of GS, namely s?nta rasa.Discourse of GS is established structurally like a diamond necklace: acarasusila-tatwa-yoga by narrating religious concept of syncretism idea of Siwa-Buddha. The philosophic thought is the three big schools of Hindu: dwaitawisisth?dwaita-adwaita. The source text is having a discourse of declarativeimperativeobjective. The hypogram is much read in term of searching and then tobee expanded. It can finally be said that GS is a literature of Hindu that fulfills therequisite of mah?k?vya in the domain of Sekar Alit bali.
Keywords: geguritan, religious literature, kàvya, yoga, sekar, aguron-guron, kàma, tirtayatra, and rasa.